1999
DOI: 10.1091/mbc.10.8.2759
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Point Mutant at Position 1 of the Influenza Hemagglutinin Fusion Peptide Displays a Hemifusion Phenotype

Abstract: We showed previously that substitution of the first residue of the influenza hemagglutinin (HA) fusion peptide Gly1 with Glu abolishes fusion activity. In the present study we asked whether this striking phenotype was due to the charge or side-chain volume of the substituted Glu. To do this we generated and characterized six mutants with substitutions at position 1: Gly1 to Ala, Ser, Val, Glu, Gln, or Lys. We found the following. All mutants were expressed at the cell surface, could be cleaved from the precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
201
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(214 citation statements)
references
References 37 publications
12
201
0
Order By: Relevance
“…The G1E mutation in intact HA also inhibits HA-mediated fusion (22,23). Our results indicate that studies of membrane fusion activity using liposomes that are at the brink of spontaneous lipid mixing, such as those of DOPC:DOPE: cholesterol (1:1:1), are not as discriminatory of the fusogenic activity of different protein constructs with different intrinsic fusogenic activity.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The G1E mutation in intact HA also inhibits HA-mediated fusion (22,23). Our results indicate that studies of membrane fusion activity using liposomes that are at the brink of spontaneous lipid mixing, such as those of DOPC:DOPE: cholesterol (1:1:1), are not as discriminatory of the fusogenic activity of different protein constructs with different intrinsic fusogenic activity.…”
Section: Resultsmentioning
confidence: 79%
“…Our results indicate that studies of membrane fusion activity using liposomes that are at the brink of spontaneous lipid mixing, such as those of DOPC:DOPE: cholesterol (1:1:1), are not as discriminatory of the fusogenic activity of different protein constructs with different intrinsic fusogenic activity. This is also indicated by the fact that there was some fusion activity of the G1E-HA2* with these liposomes, but no fusion was observed with the intact G1E mutant in the experiments on cell fusion (22).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Several mutagenesis studies indicate that the glycine at the N terminus of influenza virus HA2 fusion peptide is particularly critical, and substitution of this residue with more polar or more hydrophobic residues results in a complete loss of activity; the only tolerated change in this position appears to be an alanine. A particularly interesting mutant is G1S of HA2, because replacing the glycine with a serine facilitates lipid mixing but not content mixing (65,66). Also the ability of human immunodeficiency virus type 1 gp41 to promote membrane fusion can be completely abolished by a single mutation G10V within the fusion peptide (67).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational studies of class I viral fusion proteins have shown that simply pulling the two membranes together is not sufficient (1)(2)(3) to catalyze fusion in a physiological context: in these systems, a specific activity of the membrane-inserted peptides is required for full fusion. The precise mechanism of membrane activity has remained elusive.…”
mentioning
confidence: 99%